Surveillance for Flaviviruses Near the Mexico-U.S. Border: Co-circulation of Dengue Virus Serotypes 1, 2, and 3 and West Nile Virus in Tamaulipas, Northern Mexico, 2014-2016 - Garza-Hernandez, Javier Alfonso (2018)
A clinical, serological, and molecular investigation was performed to determine the presence of dengue virus (DENV) and other flaviviruses among residents of the city of Reynosa, Tamaulipas, on the Mexico–U.S. border in 2014–2016. The sample population consisted of 2,355 patients with suspected dengue, in addition to 346 asymptomatic individuals recruited during a household-based epidemiological investigation designed to identify flavivirus seroconversions. Sera were collected from patients with suspected dengue in the acute phase of illness and from asymptomatic individuals at enrollment and every 5–7 months for 19 months. Sera from suspected dengue patients were tested for DENV antigen by enzyme-linked immunosorbent assay (ELISA), and select antigen-positive sera were further tested using a serotype-specific, quantitative reverse transcription–polymerase chain reaction. Sera from the household cohort were tested for flavivirus-reactive antibodies by immunoglobulin (Ig) M and IgG ELISAs using DENV antigen. A total of 418 (17.7%) patients with suspected dengue had laboratory-confirmed DENV infections, including 82 patients who were positive for DENV RNA. The most frequently detected serotype was DENV-1 (61 patients), followed by DENV-2 (16 patients) and DENV-3 (five patients). A total of 217 (62.7%) asymptomatic individuals had flavivirus-reactive antibodies at enrollment, and nine flavivirus-naïve individuals seroconverted. Sera from a subset of dengue patients and household participants, including all those who seroconverted, were further tested by plaque reduction neutralization test, resulting in the detection of antibodies to DENV-1, DENV-2, and West Nile virus. In summary, we provide evidence for the co-circulation of multiple flaviviruses in Reynosa, Tamaulipas, on the Mexico–U.S. border.